Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

Synergy between ultra-high-performance fiber-reinforced concrete (UHP-FRC) and longitudinal bars in thin panels under flexure - Ke-Fan Weng; Yu-Qi Liu; Shi-Wen Han; Ji-Xiang Zhu; Bo-Tao Huang; Jing Yu (Engineering Structures, 2026)

Experimental and numerical investigation on flexural performance of ultra-high-performance fiber-reinforced concrete (UHP-FRC) hollow panels with different longitudinal reinforcements - Ke-Fan Weng; Xiao-Yi Wang; Shi-Wen Han; Yu-Qi Liu; Bo-Tao Huang; Jing Yu (Engineering Structures, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Corncob biorefinery: XOS via extrusion–microwave hydrolysis and carbon/MoS2 catalysts from residue - Jiakang Liang; Jingyi Han; Ziwei Zhu; Xingyu Fan; Yagoub Abu El-Gasim A; Man Zhou; Haoxin Li; Li Chen; Xiaojie Yu; Cunshan Zhou (Biomass and Bioenergy, 2026)

Analysis of the threshing performance through DEM simulation and machine learning for flexible wheat plants - Jianhua Fan; Jintong Xu; Lu Wang; Jianqun Yu; Zhiwu Han (Biosystems Engineering, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Mechanisms of high-humidity hot air impingement blanching (HHAIB) on microbial counts, functional properties, phenolic profile transformation, and volatile compounds in celery stalks (Apium graveolens L.) - You-Sheng Shi; Yu-Ting Ding; Jun Zhang; Jing-Shou Zhang; Shi-Han Yu; Fan Yang; Wei-Peng Zhang; Feng-Kui Xiong; Ming-Qiang Xu; Gang Shen; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Synergistic vacuum steam pulse blanching and gliding arc cold plasma pretreatment enhances drying efficiency and folate retention in Yardlong bean pods - Samuel Ariyo Okaiyeto; Fan Yang; Dan Liu; Lei Fu; Shi-Han Yu; Xiao-Xiao Niu; Feng-Lun Zhang; Cheng Zhang; Feng-Kui Xiong; Mohsen Mokhtarian; Weiqiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Adaptive seasonal management after eradicating invasive Spartina: A nature-based approach - Dong-Fan Xu; Qi Yuan; Hai-Qiang Guo; Bing Tan; Fei Quan; Zhe-Xiu Yu; Dong-Yang Han; Yu-Jiao Lu; Ying-Ying Hao; Si-Qi Zhou; Guang Ge; Bin Zhao; et al. (Ecological Engineering, 2026)

Synergistic electronic regulation induces electron spin polarization to facilitate homogeneous Li+ flux for dendrite-free lithium metal anodes - Kunyu Hao; Xiangjie Chen; Xuena Du; Chenyang Guo; Mingze Xie; Yu Lu; Pengcheng Qi; Zheng Fan; Lingyun Han; Yiwen Tang (Chemical Engineering Journal, 2026)

ROS-scavenging and immunomodulatory MXene-MnO₂ hydrogel nerve conduit for peripheral nerve regeneration - Tiankun Hui; Yajing Yang; Fei Diao; Haihan Fan; Jie Chen; Yan Li; Yingjie Song; Chenchen Fu; Meijie Jia; Wenwei Han; Tengbo Yu; Jianye Fu (Chemical Engineering Journal, 2026)

High-performance sandwiched pressure sensors enabled by the synergism of multilayer assembly of hierarchical microstructures and interlayer conductivity mismatching - Xue Han; Xi Wang; Huijiang Li; Xiaotian Song; Jinsong Wang; Kaichen Zhang; Lirong Fan; Juanjuan Wang; Xiaopeng Li; Enping Liu; Xiaoli Zhang; Bin Wang; et al. (Chemical Engineering Journal, 2026)

Engineered TGF-β-enriched exosomes delivered by dissolving microneedles for androgenetic alopecia therapy - Yu-Qing Ni; Yi-Fan Ji; Bo Huang; Si-Jia Tang; Zi-Han Fang; Li-Bin Wang; Yuan Zhang; Xing Li (Chemical Engineering Journal, 2026)

Mannan-rich oligosaccharides from spent coffee grounds using formic acid hydrolysis: production, characterization and its bioactive properties - Chang Yu; Mingyang Han; ChenJie Ji; Yuyang Fan; Jia Ouyang (Bioresource Technology, 2026)

Retraction notice to “Identification of significant live bacterial community shifts in different reclaimed waters during ozone and chlorine disinfection” [Sci. Total Environ. 896 (2023) 165199] - Qi Shi; Zhuo Chen; Han Yan; Meiying Xu; Ke-Fan Cao; Yu Mao; Xiaowen Chen; Hong-Ying Hu (Science of The Total Environment, 2026)

TME-activated MXene nanoheterojunctions engineer cancer cells through phototherapy and metabolic interference for enhanced cuproptosis and immunotherapy - Hui Li; Jie Geng; Min Mu; Susu Xiao; Chenqian Feng; Lihua Zhou; Yuanxiang Wang; Wei Yu; Rangrang Fan; Bo Han; Gang Guo (Chemical Engineering Journal, 2026)

Hypoxia-Driven Mechanisms in Ischemic Heart Failure: A Bioinformatics, Machine Learning and Bayesian Network Study - Quancheng Han; Ruiqi Fan; Jingjing Ma; Huajing Yuan; Yonghong Guo; Yitao Xue; Yiding Yu; Yan Li (Cardiovascular Toxicology, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

GNPS-guided discovery of antifungal brominated metabolites from Chaetomium elatum FH-3 via NaBr-regulation and biotransformation - Jing-jing Su; Yin-han Teng; Bai-xue Yin; Hai-fang Wang; Yu-ze Li; Wei Wang; Xiao-mei Song; Dong-dong Zhang; Hao Fan (Phytochemistry Letters, 2026)

17β-estradiol reshapes the reproductive dose–response to polystyrene nanoplastics in the rotifer Brachionus calyciflorus - Qi-bin Zhu; Yi-fan Feng; Yi-fu Xing; Yu Zhang; Jiang-hua Yang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquatic Toxicology, 2026)

Effects of Antioxidant DI-3-N-Butylphthalide on Hemorrhagic Transformation Assessed by Propensity Score Matching in a Real-World Thrombolyzed Ischemic Stroke Patient Setting - Ziqi Han; He Liang; Tieping Fan; Mario Minor Murakami Junior; Shumin Li; Ruikang Sun; Daoyong Peng; Shiwei Du; Yu Hasegawa; Haojie Gao; Dong Chen; Dirk M. Hermann; et al. (Translational Stroke Research, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Plant-specific groundwater source apportionment and health risk assessment of chemical industrial parks based on an enhanced potential pollution index framework - Junjie Li; Jingjing Yu; Bin Yang; Ping Du; Chunmei Han; Juan Chen; Bei Yuan; Yunhui Zhang; Ruibing Han; Wenxuan Fan (Journal of Hazardous Materials, 2026)

Waste cooking oil biodiesel alters combustion pathways to enhance volatile organic compound emissions and reduce intermediate/semi -volatile organic compounds in agricultural machinery - Fan Zhang; Bo Huang; Junfeng Cui; Yi Wang; Xinyi Wan; Lele Han; Gehui Wang; Yong Han; Yu Wang; Hai Guo; Min Cui (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Coupling health risk constraints and source apportionment to quantify environmental capacity consumption of soil heavy metal(loid)s in urban green spaces — A case study in Shanghai, China - Zhancheng Wang; Quanbo Yu; Huijuan Wang; Yangyang Hu; Zhen Wei; Xiaohui Luo; Tingting Xu; Rongxi Li; Zilin Han; Jiaheng Wu; Xi Zhang; Qicheng Zhong; et al. (Journal of Hazardous Materials, 2026)

Multiscale hybrid strategy for high-performance flexible pressure sensors with high sensitivity and wide working range - Ruonan Zhang; Naida Ding; Han Wang; Tian-Yu Zhang; Chaoqun Ma; Huijie Fan; Zhi Han; Chang Liu; You Zeng (Chemical Engineering Journal, 2026)

An integrated strategy for Cyclotella cryptica cultivation: From antibiotic selection to efficient mixotrophic bioprocessing - Yalan Yu; Zhichao He; Tengsheng Qiao; Sizhe Fan; Lin Zhang; Jian Li; Spiros N. Agathos; Kehou Pan; Jichang Han (Algal Research, 2026)

Speciated full-volatility organic compound emissions from typical agriculture machinery in China - Yi Wang; Lele Han; Bo Huang; Xia Xu; Xinyi Wan; Yubao Chen; Yong Han; Min Cui; Yu Wang; Hai Guo; Fan Zhang; Gehui Wang (Journal of Environmental Sciences, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Ultrasound-assisted purification of corncob xylooligosaccharides: Synergistic decolorization and citric acid removal - Jiakang Liang; Xingyu Fan; Jingyi Han; Haoxin Li; Ziwei Zhu; Li Chen; Xiaojie Yu; Hua Yang; Cunshan Zhou (Food and Bioproducts Processing, 2026)

Propyl propionate enabling stable operation of 4.55 V LiCoO2/graphite pouch cells at various temperatures via solvation and interface modulation - Shiran Li; Yu Zhang; Xiao-Zhong Fan; Xiaomeng Wang; Gupei Ding; Weiguo Li; Xu-Feng Zang; Miaomiao Han; Long Kong (Chemical Engineering Journal, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Necroptosis in pancreatic cancer: Molecular mechanisms and therapeutic implications - Yu-Jie Fan; Wei-Jia Liu; Chang Liu; Yi-Wen Zhu; Ti Chu; Hang-Shen Han; Dong-Dong Wu (Apoptosis, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Multi-omics reveal the prevalence of Thaumarchaeota and their biogeochemical roles in coastal low oxygen zones - Yu Han; Airui Wang; Zhijie Zhang; Le Liu; Quanrui Chen; Wei Fan; Ehui Tan; Kai Tang (Marine Pollution Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

Artificial humic acid promotes carbon sequestration in the rice-soil system - Zeyu ZHANG; Yu QIAO; Dongxing XIE; Jicheng HAN; Zhuqing LIU; Ying ZHAO; Fan YANG (Pedosphere, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Assessment of bioenergy crop productivity and carbon emissions mitigation potential on marginal lands in China based on the machine learning model and meta-analysis - Ziyue Yu; Hang Han; Fan Zhang (Journal of Cleaner Production, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Removal of chelated heavy metals from soil washing effluent by a sulfate-reducing bacterium and its re-washing potential - Wei Han; Yu Gao; Guixiang Zhang; Dandan Liu; Hao Wu; Lisha Fan; Xiaofang Guo; Hongbing Ji; Fengsong Zhang (Environmental Geochemistry and Health, 2026)

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

Global meta-analysis of bioenergy crops reveals substantial greenhouse gas mitigation potential - Ziyue Yu; Hang Han; Fan Zhang (Resources, Conservation and Recycling, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Balancing crop productivity and environmental benefits: The comprehensive effects of phosphate application on wheat production in China based on a meta-analysis - Fan Zhang; Xiukang Wang; Zaidong Yang; Yu Wang; Shiju Liu; Juan Han (Journal of Environmental Management, 2026)

Organic substitution improves crop productivity while mitigating the risk of soil reactive nitrogen losses: A meta-analysis of maize production in China - Fan Zhang; Yu Wang; Xiukang Wang; Chun Yan; Hao He; Shiju Liu; Guangxin Zhang; Juan Han (Journal of Environmental Management, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Mediating role of the maternal placental growth factor levels on association between ozone exposure and adverse pregnancy outcomes - Yajuan Wang; Yuanyuan Yu; Yang Li; Xiaoli Gao; Wenjun Fan; Xuening Bai; Xiaozhou Li; Jiayan Zhou; Ying Zhang; Qisijing Liu; Chen Li; Rongrong Wu; et al. (Environmental Research, 2026)

Current status, challenges, and future prospects of non-thermal sterilization technologies in dairy products - Nina Ding; Qiyue Sun; Zhongna Yu; Hongning Jiang; Qijing Du; Rongbo Fan; Liangliang You; Yongxin Yang; Rongwei Han (Critical Reviews in Food Science and Nutrition, 2026)

Thioether and ether derivatives of diphyllin: synthesis and inducing tumor ferroptosis activity - Jianhang Han; Yujie Ma; Siwei Ji; Fan Yang; Qinyao Lu; Yuting Zhang; Yu Zhao (Natural Product Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

How adsorption vs biodegradation sustains the treatability of odorous acetal/terpene in bioactive activated carbon filters - Fang Liu; Qi Wang; Ziming Han; Junzhi Zhang; Fan Lu; Yaohan Qian; Nana Bie; Yi Chen; Yingxin Gao; Min Yang; Jianwei Yu (Journal of Hazardous Materials, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Carbon dioxide as the primary greenhouse gas emission in hard clam (Meretrix taiwanica) aquaculture - Yin-Yu Chen; Wei-Sheng Zhang; Chien‑Wei Tu; Bo-Ying Chen; Wen-Ping Cheng; Zhen Hao Liao; Yi-Jung Chen; Meng-Chou Lee; Fan-Hua Nan; Han-Yang Yeh (Aquaculture International, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

An Improved Tuna Swarm Optimization Algorithm based XGBOOST Classification Method for Food Risk Evaluation - Yongming Han; Fan Yu; Jiaxin Liu; Zhen Zhang; Bo Ma; Ling Wang; Zhiqiang Geng (Swarm and Evolutionary Computation, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Substrate-driven enrichment and mining of ligninolytic bacteria for efficient lignin-to-PHA conversion - Tao Xu; Chong Han; He Liu; Zi-Yi Zhao; Fan-Li Zeng; Yu-Cheng Gu; Zhi-Hua Liu; Bing-Zhi Li (Chemical Engineering Journal, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Large eddy simulation and laboratory experiments of ice melting in steady currents and surface waves - Chia-Ren Chu; Cheng-Han Yu; Fang-Yu Fan; Hwa Chien; Tso-Ren Wu (Cold Regions Science and Technology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

New insights for microplastic degradation: Synergistic degradation mechanisms of microplastics and atrazine in sediments - Cheng Yang; Jinjiang Duan; Jianhao Song; Yu Xiang; Ruxin Yang; Xiangtian Man; Yuanyuan Feng; Dongdong Gao; Mengli Chen; Qingping Zou; Meikun Fan; Han Zhang (Water Research, 2025)

Effect of lipid oxidation on the color deterioration of ready-to-eat oysters: Discussion based on the model system - Ying Luo; Jie Xu; Ying-Chen Fan; Zong-Han Wang; Yuan-Yuan Hu; De-Yang Li; Yu-Xin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Vacuum-steam pulsed blanching enhances drying, nutrient retention, and anti-nutritional factor reduction in Vigna unguiculata - Samuel Ariyo Okaiyeto; Shi-Han Yu; Haiou Wang; Jin-Hong Zhao; Cun-Shan Zhou; Ahmed Jamilu Mustapha; An-An Zhang; Fan Yang; Jing-Shou Zhang; Hong-Wei Xiao (Food Chemistry, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Short-term effects of atmospheric oxidative capacity (Ox) on total, acute and chronic respiratory mortalities, and its modification on fine particle's effects - Ruosu Zhang; Dongxia Jiang; Zhaokun Wang; Yi Fan; Xueqiong He; Jianhui Guo; Yaqi Wang; Xinyao Lian; Ziqi Tang; Hao Yu; Renqiang Han; Jin Ye; et al. (Atmospheric Environment, 2025)

SHAP explainable PSO-CNN-BiLSTM for 6-hour prediction analysis of urban PM2.5 and O3 concentrations - Kun Lei; Mingya Wang; Mingshi Wang; QingWei Liu; Fan Zhang; MingFei Xing; Wei Wu; Fengcheng Jiang; Xiaoming Guo; Qiao Han; Fayang Guo; Huiyun Pan; et al. (Atmospheric Pollution Research, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Identification and characterization of the first G8P[1] sheep rotavirus strain in China: Genetic similarity to human rotavirus and zoonotic potential - DengShuai Zhao; Ping Li; Junyan Fu; YuanHang Zhang; MiaoMiao Zhang; TianYu Wang; DiXi Yu; Han Gao; LiMei Qin; MengMeng Zhao; Feng Wen; ShengFeng Chen; et al. (Veterinary Microbiology, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Invasive plant-derived low-cost Fe-Co hydrochar for singlet oxygen-dominated sulfamethoxazole degradation: Performance, mechanism and life cycle assessment - Yu-Han Fan; Yu-Wei Lu; Jun Ma; Yang Yi; Min Zhou; Hua-Juan Wang (Journal of Cleaner Production, 2025)

Combined impact of land-use/land-cover and soil property changes on soil erosion in the Yellow River Basin - Yang-Yang Wang; Xin-Xiao Yu; Deng-xing Fan; Guo-Dong Jia; Jian-Zhi Niu; Yong-Han Feng; Yu-Kun Wang (Journal of Environmental Management, 2025)

Development of an integrated hydro-mechanical coupling test system for meter-scale fractured rock masses in laboratory - Aiqing Wu; Lei Fan; Jiming Gao; Yuankun Liu; Guoqing Guo; Xiaoyu Han; Wei Hu; Meiwang Yu (International Journal of Rock Mechanics and Mining Sciences, 2025)

A novel approach to sesame oil aroma generation: Synergy of enzyme-modified lipids and the Maillard reaction - Bei-bei Hu; Wen-ting Yin; Tong Yu; Zi-qi Han; Yu-xin Liu; Hua-min Liu; Xiao-shuang Cai; Zhuo-qing Zhai; Fan Zhang (Food Chemistry, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

Lysine functionalization regulates the electronic structure and reaction microenvironment of Cu2O for efficient and stable nitrite electroreduction - Xiao-Hui Wang; Yi-Ting Yang; Yue-Han Qin; Fan Yang; Yu Chen; Shu-Ni Li (Chemical Engineering Journal, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Regulating charge separation by structure adjusting in pyrene-based 1D COFs for efficient photocatalytic hydrogen evolution - Bing Han; Shuyan Wang; Xianglin Yu; Xuxin Fan; En Liang; Yao Yang; Huan Zhang; Changyu Qin; Junbo Li (Chemical Engineering Journal, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

Peripheral blood RNA modifications as a novel diagnostic signature for polycystic ovary syndrome - Liwen Zhang; Xinxin Liu; Yu Zhang; Lang Qin; Shijia Pan; Xueqi Yan; Sen Dong; Zerong Feng; Song-jia Fan; Rusong Zhao; Xueying Gao; Shigang Zhao; et al. (Science China Life Sciences, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Variations in quality attributes of cow and goat milk subjected to microwave and high-pressure treatments over a two-week storage period - Nina Ding; Qiyue Sun; Zhongna Yu; Qijing Du; Rongbo Fan; Guangxu Ren; Liangliang You; Shuo Feng; Yongxin Yang; Rongwei Han (Innovative Food Science & Emerging Technologies, 2025)

Microscopic influence mechanisms of tetra-n-butylammonium bromide on hydrate growth and stability in saline environment - Fangning Fan; Han Jia; Yihan Huang; Zhenghao Kou; Ruitong Xu; Haowen Yu; Yuanbo Wang; Xu Li; Bowen Wang; Zhe Wang; Yurong Zhao (Gas Science and Engineering, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Dynamic changes in physicochemical, bacterial, and volatile profiles during kombucha fermentation of mulberry fruits and leaves - Chunyu Xu; Zhongna Yu; Shichu Zhou; Huixue Feng; Qijing Du; Xue Yuan; Rongbo Fan; Hongning Jiang; Yongxin Yang; Rongwei Han; Xiaxia Wang (Food Research International, 2025)

Comparative evaluation of selected adjuvants for possible application of Aeromonas caviae inactivated vaccine in crucian carp (Carassius auratus) - Han Lu; Tao-luo Tao; Yu-Long Liu; Fan Jia; Yi-feng Cui; Xiao-feng Shan (Aquaculture International, 2025)

The Systematic Study on the Effects of Adding Bile Acids and Zinc to Laying Hens’ Diets: From Production Performance to Egg Quality, Trace Element Content, and Intestinal Microorganisms - Shou Kang Cao; Yi Fan Li; Han Chen; Yu Qing Mu; Xue Zhuang Wu (Biological Trace Element Research, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

Enhancing stability and PEC performance of TiO2 for Bias-Free seawater splitting with an FeS layer and In-Situ FeOOH Regeneration - Dabo Liu; Shanshan Jiang; Ran Tao; Zhenming Chu; Xiaoxing Fan; Yu Han (Fuel, 2025)

Retraction Note: Effect of Danhong injection on pharmacokinetics and pharmacodynamics of rivaroxaban in rats - Weihong Yin; Jiao Li; Zhaoyang Han; Siwen Wang; Fan Wu; Chao Yu; Xueying Yan; Mingyu Cui (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Innovative strategy for dechlorination of halogenated organic Pollutants: Microbial-Derived formate production and Immobilized-PdNP biosynthesis - Yang-Yang Fan; Wen-Wen Liu; Yu-Han Chai; Jing Huang; Min Wang; Xin Wang; Xin-Lu Cai; Li Zhang; Xiang Xiao (International Biodeterioration & Biodegradation, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Bioactive multifunctional hydrogel to ameliorate adverse joint microenvironment and enhance cartilage regeneration - Zhang Po; Ma Xiao; Zhang Han; Liu Yang; Zhu Liang; Bi Yanchi; Wang YiHu; Shen Zhan; Wang Jian; Jiang Fan; Zhu Xuesai; Yao Yizhi; et al. (Chemical Engineering Journal, 2025)

PCBP2 in gastrointestinal cancers: fundamental mechanism and clinical potential - Chenyang Wang; Xi Chen; Lili Duan; Junfeng Chen; Liaoran Niu; Siyu Wei; Han Bai; Yujie Zhang; Wei Zhou; Jinqiang Liu; Wanli Yang; Yu Han; et al. (Journal of Molecular Medicine, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Brain structural reorganization mediates the relationship between hearing loss and cognitive impairment - Yao Wang; Jianfen Luo; Wenqing Li; Yu Han; Wen Ma; Siqi Liu; Lei Xu; Zhaomin Fan; Yu Ai; Meixia Su; Fuxin Ren; Fuyan Li; et al. (Brain Imaging and Behavior, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Life cycle assessment-guided development of iron-based biomass catalyst for sustainable tetracycline degradation - Yu-Qi Li; Yu-Han Fan; Jun Ma; Ming Chen (Process Safety and Environmental Protection, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

3D facial imaging: a novel approach for metabolic abnormalities risk profiling - Qianqian Peng; Yam Ki Cheung; Yu Liu; Yiyang Wang; Jingze Tan; Yajun Yang; Jiucun Wang; Jing-Dong J. Han; Li Jin; Fan Liu; Sijia Wang (Science China Life Sciences, 2025)

Identification of nodule-inception-like protein (NLP) transcription factor family and analysis of their expression under abiotic stresses in Rhododendron henanense subsp. lingbaoense - Xiangli Yu; Yonghui Li; Wenwen Fan; Junwang Han; Yafang Zhang; Hailiang Wang; Xiaojun Zhou (Plant Biotechnology Reports, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Bicyclic polyprenylated acylphloroglucinol-related meroterpenoids as potent DRAK2 inhibitors from Hypericum patulum - Jin-Chang Huang; Xin-Yu Jia; Yi-Fan Lv; Hong-Hong Xu; Ming Han; Qiang-Qiang Yu; Yu-Ting Lu; Hong-Xun Yang; Yang Yang; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

RETRACTED ARTICLE: Effect of Danhong injection on pharmacokinetics and pharmacodynamics of rivaroxaban in rats - Weihong Yin; Jiao Li; Zhaoyang Han; Siwen Wang; Fan Wu; Chao Yu; Xueying Yan; Mingyu Cui (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Exploring trench of clay with submerged moving circular vertical jet: Numerical analysis - Zeren Fan; Long Yu; Yunrui Han; Qing Yang (Ocean Engineering, 2025)

Preparation of waste toner-derived magnetic adsorbent for analysis of lead in aqueous and oil-based foods - Long Qin; Yue Wang; Tingjiang Wan; Weian Fan; Han Jiang; Bin Zhang; Yiwei Wu; Xiaoxiao Yu; Chuan Wang (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Efficiently selective inactivation of Gram-positive bacteria by MCM-41 molecular sieve-supported copper-based self-cascading nanozymes - Xue-Yao Pang; Fan-Xiang Meng; Cheng Ma; Si-Yang Ni; Zi-Han Jia; Bo Li; Yu-Xiang Liu; Wei-Wei Gao (Chemical Engineering Journal, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Vertical canopy structure dominates cooling and thermal comfort of urban pocket parks during hot summer days - Si-Qi Zhou; Zhao-Wu Yu; Wei-Yuan Ma; Xi-Han Yao; Jun-Qi Xiong; Wen-Juan Ma; Shu-Yao Xiang; Qi Yuan; Ying-Ying Hao; Dong-Fan Xu; Ben-Yao Wang; Bin Zhao (Landscape and Urban Planning, 2025)

CO2 hydrogenation to methanol over Cu-CeO2-ZrO2 catalysts: The significant effect of metal-support interaction - Jian Han; Lei Wang; Jun Yu; Maohong Fan; Dongsen Mao (Fuel, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

The PhoBR two-component system upregulates virulence in Aeromonas dhakensis C4–1 - Wei Feng; Xuesong Li; Nuo Yang; Lixia Fan; Guiying Guo; Jun Xie; Xiuqing Cai; Yuqi Meng; Jifeng Zeng; Yu Han; Jiping Zheng (Aquaculture, 2025)

Nitrite and sulfide stress affects physiological and metabolic functions of gills in crab Eriocheir sinensis - Yi-fu Xing; Yi-fan Feng; Jian Tian; Yu Zhang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquaculture, 2025)

Simulating wind prevention and sand fixation service flow in arid Inland River basins: Insights from the Tarim River basin, China - Wei Yu; Xiaofei Ma; Yonghui Wang; Wei Yan; Chun Luo; Yonglong Han; Binbin Fan (Science of The Total Environment, 2025)

Disentangling the contributions of water vapor, albedo and evapotranspiration variations to the temperature effect of vegetation greening over the Arctic - Linfei Yu; Guoyong Leng; Lei Yao; Chenxi Lu; Siqi Han; Shunxiang Fan (Journal of Hydrology, 2025)

Integrative analysis of transcriptome and proteome wide association studies prioritized functional genes for obesity - Qi-Gang Zhao; Xin-Ling Ma; Qian Xu; Zi-Tong Song; Fan Bu; Kuan Li; Bai-Xue Han; Shan-Shan Yan; Lei Zhang; Yuan Luo; Yu-Fang Pei (Human Genetics, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Dual-directional regulation of extracellular respiration in Shewanella oneidensis for intelligently treating multi-nuclide contamination - Xin-Lu Cai; Xuan Yao; Li Zhang; Yu-Han Chai; Xuan Liu; Wen-Wen Liu; Ruo-Xi Zhang; Yang-Yang Fan; Xiang Xiao (Journal of Hazardous Materials, 2024)

Microplastics and benthic animals reshape the geochemical characteristics of dissolved organic matter by inducing changes in keystone microbes in riparian sediments - Yuanyuan Feng; Jinjiang Duan; Cheng Yang; Qingping Zou; Ziwei Chen; Jia Pu; Yu Xiang; Mengli Chen; Meikun Fan; Han Zhang (Environmental Research, 2024)

Hinokiflavone from Platycladi cacumen as a potent broad-spectrum inhibitor of gut microbial Loop-1 β-glucuronidases: Inhibition kinetics and molecular simulation - Yue Han; Yu-Tong Liu; Lu Chen; Hao-Fan Sun; Guang-Hao Zhu; Dong-Ning Kang; Qi Zhou; Hui Tang; Yu-Ling Yin; Jie Hou (Chemico-Biological Interactions, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

A novel variant (p.A524P) in Spastin is responsible for a Chinese family with hereditary spastic paraplegia - Yu-Han Jin; Yang-Ziyu Xiang; Mei-Fang Zhao; Yi-Hui Liu; Liang-Liang Fan; Xiao-Cong Li (Molecular Biology Reports, 2024)

Organic carbon decomposition temperature sensitivity positively correlates with the relative abundance of copiotrophic microbial taxa in cropland soils - Yuan Du; Anlan Yu; Yuan Chi; Zelin Wang; Xinrui Han; Kaifang Liu; Qiuping Fan; Xin Hu; Rongxiao Che; Dong Liu (Applied Soil Ecology, 2024)

Organic carbon cycling in the sediments of Prydz Bay, Eastern Antarctica: Implications for a high carbon sequestration potential - Peisong Yu; Dong Li; Jun Zhao; Jianming Pan; Ji Hu; Haifeng Zhang; Jianfeng He; Zhengbing Han; Xufeng Yang; Cai Zhang; Gaojing Fan; Haisheng Zhang (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

A high-permeability method for extracting purple yam saponins based on ultrasonic-assisted natural deep eutectic solvent - Yu-Jiao Hou; Peng-wei Wang; Han Zhang; Ying-Ying Fan; Xu Cao; Yan-Qiong Luo; Qian Li; Mosesmanaanye Njolibimi; Wen-jing Li; Bo Hong; Chun-jie Zhao (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Introducing electron-rich thiophene bridges in hot exciton emitter for efficient non-doped near-infrared OLEDs with low turn-on voltages - Ruming Jiang; Zhangshan Liu; Yuanyuan Han; Jiawei Long; Ting Guo; Xia Lan; Mingguang Yu; Ting Fan; Haijun Ma; Yen Wei; Ben Zhong Tang; Zujin Zhao (Chemical Engineering Journal, 2024)

Analysis of the Polyculture Model of the Bivalves Anadara broughtonii and Chlamys farreri in Suspension Cages in Shallow Seas - Chunnuan Zhao; Liqun Ren; Shuai Xu; Yuping Wu; Haiying Han; Bo Li; Yanxin Zheng; Yang Chen; Xiwen Wang; Nini Fan; Junjie Li; Chaoyi Xie; et al. (Fishes, 2024)
This study examined the survival rates of Anadara broughtonii and Chlamys farreri with varying heights throughout winter and summer aquaculture periods under varying ratios of mixed-culture conditions in marine environments. The aim was to assess the viability and economic advantages of mixed-culture practices among different bivalve species. Results indicate that the winter (from December to February of the following year) mortality rate for A. broughtonii in mixed culture ranges from 12.04% to 16.85%, markedly lower than in single-species cultures. Mixed-culture A. broughtonii measuring 2.5–4.0 cm exhibit a significantly reduced summer (from July to September) mortality rate compared to those in single-species cultures (p

Experimental Investigation of Wave Pressure on Breakwater-Integrated Oscillating Water Column Devices with a Perforated Wall - Chun-Han Ko; Chun-Yu Fan; Ching-Piao Tsai (Journal of Marine Science and Engineering, 2024)
This study investigates the wave pressure on an Oscillating Water Column (OWC) device, which features a perforated wall positioned in front of the OWC chamber and is integrated with a caisson breakwater. The perforated wall is designed to mitigate wave impacts on the OWC device under storm wave conditions. To achieve this, a series of laboratory experiments were conducted using a 1:25 scale model, considering both regular and irregular waves. Wave pressure measurements and analyses were performed on various configurations to assess the effects of the perforated wall on the wave pressure exerted against the front wall of the OWC chamber and the caisson breakwater. The results indicate that the perforated wall effectively reduces the amplitude of water column oscillations within the OWC chamber during storm conditions, thereby significantly reducing wave pressure on the OWC chamber wall by approximately 14% and on the breakwater by about 20.3%.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Quorum sensing mediated response mechanism of anammox consortia to anionic surfactant: Molecular simulation and molecular evidence - Xue-Ping Wang; Na-Na Han; Zi-Yan Xu; Yu-Hui Zhu; Gui-Feng Li; Nian-Si Fan; Ren-Cun Jin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Advanced Human Reliability Analysis Approach for Ship Convoy Operations via a Model of IDAC and DBN: A Case from Ice-Covered Waters - Yongtao Xi; Xiang Zhang; Bing Han; Yu Zhu; Cunlong Fan; Eunwoo Kim (Journal of Marine Science and Engineering, 2024)
The melting of Arctic ice has facilitated the successful navigation of merchant ships through the Arctic route, often requiring icebreakers for assistance. To reduce the risk of accidents between merchant vessels and icebreakers stemming from human errors during operations, this paper introduces an enhanced human reliability assessment approach. This method utilizes the Dynamic Bayesian Network (DBN) model, integrated with the information, decision, and action in crew context (IDAC) framework. First, a qualitative analysis of crew maneuvering behavior in scenarios involving a collision with the preceding vessel during icebreaker assistance is conducted using the IDAC model. Second, the D–S evidence theory and cloud models are integrated to process multi-source subjective data. Finally, the human error probability of crew members is quantified using the DBN. The research results indicate that during convoy operations, the maximum probability that the officer on watch (OOW) chooses an incorrect deceleration strategy is 8.259×10−2 and the collision probability is 4.129×10−3. Furthermore, this study also found that the factors of Team Effectiveness and Knowledge/Abilities during convoy operations have the greatest impact on collision occurrence. This research provides important guidance and recommendations for the safe navigation of merchant ships in the Arctic waters. By reducing human errors and adopting appropriate preventive measures, the risk of collisions between merchant ships and icebreakers can be significantly decreased.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Control of carbon dioxide exchange fluxes by rainfall and biological carbon pump in karst river–lake systems - Chaowei Lai; Zaihua Liu; Qingchun Yu; Hailong Sun; Fan Xia; Xuejun He; Zhen Ma; Yongqiang Han; Xing Liu; Pengyun Hao; Qian Bao; Mingyu Shao; et al. (Science of The Total Environment, 2024)

Impact and mechanism of bubble discharge plasma on ammonia nitrogen in wastewater - Ranran Wang; Fan Zhang; Zhuran Hu; Feng Han; Bin Guo; Koichi Takaki; Kefeng Yu; Chengxia Miao; Qin Hou (Journal of Water Process Engineering, 2024)

Genome-wide identification, characterization, molecular evolution and expression profiling analysis of scavenger receptors in black rockfish (Sebastes schlegelii) - Zhentao Chen; Xuangang Wang; Gan Yu; Jingrun Pu; Xuechen Li; Ze Tao; Zhixiang Duan; Fan Zhang; Ping Han; Hengshun Li; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Melanin-based duplex Cas9 ribonucleoprotein nanomedicine for synergistic phototherapy and immunotherapy - Liansheng Fan; Suchen Qu; Jing Qian; Gaoyu Shi; Qiqing Huang; Yanni Song; Yu Ji; Quli Fan; Xin Han (Chemical Engineering Journal, 2024)

Highly sensitive formaldehyde gas sensor based on SnO2/Zn2SnO4 hybrid structures - Guijun Fan; Jian Guan; Hang Yu; Qiuyi Zhu; Ning Han; Jinhan Mo; Yunfa Chen (Building and Environment, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Gain-of-function variants in GSDME cause pyroptosis and apoptosis associated with post-lingual hearing loss - Yun Xiao; Lei Chen; Kaifan Xu; Meijuan Zhou; Yuechen Han; Jianfen Luo; Yu Ai; Mingming Wang; Yu Jin; Ruifeng Qiao; Shuhui Kong; Zhaomin Fan; et al. (Human Genetics, 2024)
Gasdermin E (GSDME), a member of the gasdermin protein family, is associated with post-lingual hearing loss. All GSDME pathogenic mutations lead to skipping exon 8; however, the molecular mechanisms underlying hearing loss caused by GSDME mutants remain unclear. GSDME was recently identified as one of the mediators of programmed cell death, including apoptosis and pyroptosis. Therefore, in this study, we injected mice with GSDME mutant (MT) and examined the expression levels to assess its effect on hearing impairment. We observed loss of hair cells in the organ of Corti and spiral ganglion neurons. Further, the N-terminal release from the GSDME mutant in HEI-OC1 cells caused pyroptosis, characterized by cell swelling and rupture of the plasma membrane, releasing lactate dehydrogenase and cytokines such as interleukin-1β. We also observed that the N-terminal release from GSDME mutants could permeabilize the mitochondrial membrane, releasing cytochromes and activating the mitochondrial apoptotic pathway, thereby generating possible positive feedback on the cleavage of GSDME. Furthermore, we found that treatment with disulfiram or dimethyl fumarate might inhibit pyroptosis and apoptosis by inhibiting the release of GSDME-N from GSDME mutants. In conclusion, this study elucidated the molecular mechanism associated with hearing loss caused by GSDME gene mutations, offering novel insights for potential treatment strategies.

A temperature compensated fiber probe for highly sensitive detection in virus gene biosensing - Xiaopeng Han; Yu Zhang; Yundong Zhang; Qinghao Song; Wuliji Hasi; Siyu Lin; Fan Wang (Analytica Chimica Acta, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Microbial communities overwhelm environmental controls in explaining nitrous oxide emission in acidic soils - Shengwen Xu; Yongxiang Yu; Haoxin Fan; Nataliya Bilyera; Xiangtian Meng; Jiantao Xue; Zhong Lu; Zhihan Yang; Stephen J. Chapman; Fuyun Gao; Wenyan Han; Yaying Li; et al. (Soil Biology and Biochemistry, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Bridging the buried interface with conjugated molecule for highly efficient carbon-based inorganic CsPbI2Br perovskite solar cells fabricated in air - Yifei Shi; Lei Zhang; Shuming Hu; Xu Wang; Jiajia Han; Jincheng Huang; Junjie Chen; Yuanfang Zhang; Xinlong Zhang; Jintao He; Hengzhi Zuo; Jiayao Ju; et al. (Chemical Engineering Journal, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Solving the multi-objective path planning problem for mobile robot using an improved NSGA-II algorithm - Peng Duan; Zhenao Yu; Kaizhou Gao; Leilei Meng; Yuyan Han; Fan Ye (Swarm and Evolutionary Computation, 2024)

Biogeographic effects shape soil bacterial communities across intertidal zones on island beaches through regulating soil properties - Mingshan Xu; Xiaodong Yang; Jie Shao; Junbao Huang; Wenzhou Fan; Anna Yang; Hang Ci; Yongju Wang; Jianjun Gan; Yu Han; Jian Zeng (Science of The Total Environment, 2024)

Co-migration behavior of toluene coupled with trichloroethylene and the response of the pristine groundwater ecosystems – A mesoscale indoor experiment - Shuxuan Wu; Yu Yang; Zhifei Ma; Fan Feng; Xiangjian Xu; Sheng Deng; Xu Han; Beidou Xi; Yonghai Jiang (Journal of Hazardous Materials, 2024)

Melatonin application during cryopreservation improves the development and clinical outcomes of human vitrified–warmed oocytes - Chao Zhang; Dandan Yang; Ding Ding; Yongqi Fan; Han Yang; Jing Wang; Huijuan Zou; Bihua Rao; Qiushuang Wang; Tingting Ye; Min Yu; Zhiguo Zhang (Cryobiology, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Accurate prediction bioaccessibility of PAHs in soil-earthworm system by novel magnetic solid phase extraction technique - Yu-Han Fan; Shi-Bin Qin; Xiao-Xuan Mou; Xiao-Shui Li; Shi-Hua Qi (Chemosphere, 2024)

Construction of integrated oxygen-rich carbon-based metal-free cathode to simultaneous boost wastewater treatment performance and energy recovery in bio-electro-Fenton system - Ruyan Chen; Mengsha Han; Yaning Shi; Wei Guo; Yuhan Wu; Tianduo Zhang; Xiao Han; Cuiwei Du; Chongfei Yu; Jinglan Feng; Shuying Dong; Jianhui Sun; et al. (Chemical Engineering Journal, 2024)

A Three-dimensional Anisotropic Creep Model for Predicting the Time-dependent Deformation of Layered Rock Mass - Shuling Huang; Jinxin Zhang; Xiuli Ding; Gang Han; Peiyang Yu; Xuanting Fan (Rock Mechanics and Rock Engineering, 2024)

Enhancing urban blue-green landscape quality assessment through hybrid genetic algorithm-back propagation (GA-BP) neural network approach: a case study in Fucheng, China - Ding Fan; Nor Zarifah Binti Maliki; Siwei Yu; Fengcheng Jin; Xinyan Han (Environmental Monitoring and Assessment, 2024)
This study employs an artificial neural network optimization algorithm, enhanced with a Genetic Algorithm-Back Propagation (GA-BP) network, to assess the service quality of urban water bodies and green spaces, aiming to promote healthy urban environments. From an initial set of 95 variables, 29 key variables were selected, including 17 input variables, such as water and green space area, population size, and urbanization rate, six hidden layer neurons, such as patch number, patch density, and average patch size, and one output variable for the comprehensive value of blue-green landscape quality. The results indicate that the GA-BP network achieves an average relative error of 0.94772%, which is superior to the 1.5988% of the traditional BP network. Moreover, it boasts a prediction accuracy of 90% for the comprehensive value of landscape quality from 2015 to 2022, significantly outperforming the BP network’s approximate 70% accuracy. This method enhances the accuracy of landscape quality assessment but also aids in identifying crucial factors influencing quality. It provides scientific and objective guidance for future urban landscape structure and layout, contributing to high-quality urban development and the creation of exemplary living areas.

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

A novel p-type CoSe2 co-catalyst cooperated with hematite for boosting photoelectrochemical water splitting - Shanshan Jiang; Dabo Liu; Dongke Li; Mengyuan Xiao; Yunchou Deng; Yu Han; Ran Tao; Xiaoxing Fan; Kuiyong Liu (Fuel, 2024)

Surface-enriched Co engineering promoting electronic conductivity for single-crystalline Ni-based layered oxide cathodes - Yuhao Liang; Xiaopei Zhu; Xiaomeng Fan; Dabing Li; Feifei Xu; Han Yu; Li-Zhen Fan (Chemical Engineering Journal, 2024)

Bioelectricity and CO2-to-butyrate production using photobioelectrochemical cells with bio-hydrogel - Zhen Fang; Han Chen; Yu-Qing Wei; Qichao Fan; Ma-Wei Zhu; Yafei Zhang; Junying Liu; Yang-Chun Yong (Bioresource Technology, 2024)

Correlation Between Blood Cadmium Levels and Platelet Characteristics, As Well As Their Impact on Susceptibility to Coronary Heart Disease: Findings from NHANES 2005–2018 Data - Jichen Ci; Yuze Zhai; Benjun Wang; Weiwei Han; Bianfang Yu; Fan An (Cardiovascular Toxicology, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Multifunctional hollow spherical delafossite: Massive electrocatalyst for water splitting and photocatalytic degradation of furaltadone antibiotic wastewater - Yu-Feng You; Dhanapal Vasu; Jiaxin Jiang; Yung-Chieh Liu; Chun-Han Tsang; Te-Wei Chiu; Liangdong Fan (Journal of Water Process Engineering, 2024)

In situ reversible assembly of atomic interfacial structure in BiOI/Bi5O7I p-n heterojunctions to promote visible-light photocatalysis - Hongjian Yu; Zhiyong He; Yan Zhang; Li Shiuan Ng; Jingren Ni; Fan Guo; Jun Hu; Hiang Kwee Lee; Jie Han (Chemical Engineering Journal, 2024)

Investigating the Causes of a Rapid Gravity Decrease at the Luzhou Observatory - Zhongya Li; Yong Wang; Lelin Xing; Minzhang Hu; Yufei Han; Jiansheng Yu; Chi Xiao; Fan Wang; Jiapei Wang; Jian Wang; Xinlin Zhang (Pure and Applied Geophysics, 2024)

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Sodium nitroprusside (SNP) treatment increases the postharvest resistance of apple fruit to Alternaria alternata by enhancing antioxidant enzyme activity - Jie Han; Yingying Fan; Tao Sun; Jing An; Yu Ding; Weiwei Zhang; Fengjuan Liu; Cheng Wang (Physiological and Molecular Plant Pathology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Insight into differences in whey proteome from human and eight dairy animal species for formula humanization - Zhongyuan Ji; Ruifeng Dong; Qijing Du; Hongning Jiang; Rongbo Fan; Dengpan Bu; Jun Wang; Zhongna Yu; Rongwei Han; Yongxin Yang (Food Chemistry, 2024)

Membrane fouling mitigation and EPS reduction by CNTs-TiO2-PEDOT modified anode-membrane in Membrane Electro-Bioreactor (MEBR) treating mariculture wastewater - Jing Song; Yihan Li; Shihan Wang; Rui Han; Yu Ba; Ying Liu; Shengqiang Fan (Desalination, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

MiR-23a promotes autophagy of yak cumulus cells to alleviate apoptosis via the apoptosis signal-regulating kinase 1/c-Jun N-terminal kinase pathway - Xiaohong Han; Sijiu Yu; Yan Cui; Jingjing Li; Jiangfeng Fan; Libin Wang; Meng Wang; Yangyang Pan; Gengquan Xu (Theriogenology, 2023)

Exopolysaccharide from Bifidobacterium breve alleviate dextran sulfate sodium-induced colitis in mice via inhibiting oxidative stress and regulating intestinal flora - Meng-Meng Niu; Huan-Xin Guo; Jun-Wu Cai; Bo-Fan Duan; Yu-Han Chen; Xiang-Chen Meng (Food Bioscience, 2023)

Exposure to copper induces endoplasmic reticulum (ER) stress-mediated apoptosis in chicken (Gallus gallus) myocardium - Feiyang Ma; Xinyan Ma; Fan Yang; Jianzhao Liao; Na Qiao; Wenlan Yu; Qingyue Han; Ying Li; Jiaqiang Pan; Lianmei Hu; Jianying Guo; Zhaoxin Tang (Veterinary Research Communications, 2023)

Centralized health management based on hot spring resort improves physical examination indicators and sleep quality in people at high risk of chronic diseases: a randomized controlled trial - Yu Chen; Fan Luo; Lingli Han; Qizhong Qin; Qing Zeng; Xiangjun Zhou; Ying Huang; Qiuyidi Gao; Wen Wang; Qiuling Shi; Qirui Wang; Zhaoxia Yu; et al. (International Journal of Biometeorology, 2023)

Molecular insights into complexation between protein and silica: Spectroscopic and simulation investigations - Ting Jiang; Xiao-Fan Hu; Yan-Fang Guan; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

Recycling of discarded face masks for modification and use in SBS-modified bitumen - Xinyu Li; Fuhu Han; Shencheng Fan; Yu Liu; Jieyu Zhang; Jing Li (Environmental Science and Pollution Research, 2023)

RETRACTED: Identification of significant live bacterial community shifts in different reclaimed waters during ozone and chlorine disinfection - Qi Shi; Zhuo Chen; Han Yan; Meiying Xu; Ke-Fan Cao; Yu Mao; Xiaowen Chen; Hong-Ying Hu (Science of The Total Environment, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Overcoming slow removal efficiency-induced highly toxic I-DBPs in water by oxygen vacancies enriched invasive plant biochar catalyst: Experimental and theoretical studies - Yu-Han Fan; Yu-Wei Lu; Faisal Hayat; Yu-Han Mei; Ming Chen (Journal of Hazardous Materials, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

Hippocampal LIMK1-mediated Structural Synaptic Plasticity in Neurobehavioral Deficits Induced by a Low-dose Heavy Metal Mixture - Fankun Zhou; Lu Ouyang; Qi Li; Shuo Yang; Sisi Liu; Han Yu; Qiyue Jia; Shaoqi Rao; Jie Xie; Guihua Du; Chang Feng; Guangqin Fan (Molecular Neurobiology, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Arsenic pollution, geochemical fractions, and leaching characteristics in soil samples from four contaminated sites in the Beijiang River Basin, South China - Yu-Zhong Liu; Jun-Feng Wang; Han-Yun Fan; Tao He; Dao-Yuan Wang; Huan-Zhan Zhou; Qu-Sheng Li (Environmental Science and Pollution Research, 2023)

Study on the effect of bubble number on the collapse of a multi-bubble system near the rigid wall - Sen Han; Yaxin Huang; Wenwei Fan; Qiyan Wang; Tinglin Huang; Yu Li (Ocean Engineering, 2023)

Alleviating eutrophication by reducing the abundance of Cyanophyta due to dissolved inorganic carbon fertilization: Insights from Erhai Lake, China - Chaowei Lai; Zhen Ma; Zaihua Liu; Hailong Sun; Qingchun Yu; Fan Xia; Xuejun He; Qian Bao; Yongqiang Han; Xing Liu; Haibo He (Journal of Environmental Sciences, 2023)

Multilevel resistive switching memristor based on silk fibroin/graphene oxide with image reconstruction functionality - Shubin Liu; Yu Cheng; Fang Han; Suna Fan; Yaopeng Zhang (Chemical Engineering Journal, 2023)

MIL-101(Cr) loaded simple ILs for efficient ammonia capture and selective separation - Guopeng Han; Fenghai Li; Mingxi Guo; Hongli Fan; Qianqian Guo; Gangqiang Yu (Chemical Engineering Journal, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

A fractional-order two-surface plasticity model for over-consolidated clays and its application to deep gallery excavation - Wei Cheng; Ren-Peng Chen; Zhen-Yu Yin; Han-Lin Wang; Fan-Yan Meng (Computers and Geotechnics, 2023)

Late Pleistocene zinc isotopic indices of paleoproductivity variations in the tropical West Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Liang Du; Yipeng Wang; Yujin Fan; Rui Zhang; Tiegang Li; James Russell; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; et al. (CATENA, 2023)

Digested extracellular DNA shortens the anodic startup of microbial electrolysis cell - Xiangyu Han; Jiaman Wang; Jingjing Zhang; Baohong Han; Ning Mei; Runchuan Fan; Jing Zhao; Hong Yao; Xiaohua Yu; Weiwei Cai (Science of The Total Environment, 2023)

Human milk whey glycoprotein N-glycans varied greatly among different maternal secretor status - Xiaoqin Wang; Wenqing Li; Zhenhua Li; Tianjiao Han; Jinqiao Rong; Jiangbo Fan; Linjuan Huang; Yu Lu; Zhongfu Wang (Carbohydrate Polymers, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

The interfacial destabilization of bile salt-emulsified oil droplets, essential for lipase function, is mediated by Lycium barbarum L. leaf polysaccharides - Na Zhang; Xue Han; Rumeng Yu; Xiaomin Tang; Bo Zhang; Yanyan Zhang; Xiaoyu Yin; Wenrui Ni; Mengze Wang; Bolin Zhang; Junfeng Fan (Food Hydrocolloids, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Evaluation of the distribution and mobility of labile phosphorus in sediment profiles of Lake Nansi, the largest eutrophic freshwater lake in northern China - Ye Zheng; Yu Sun; Zhihong Zhang; Chao Han; Zhaode Wang; Cheng Liu; Fan Ke; Lei Zhang; Qiushi Shen (Chemosphere, 2023)

Two new monoterpenoids from the stems of Ephedra sinica - Chen He; Yan-gang Cao; Meng-nan Zeng; Yu-han Zhang; Ying-jie Ren; Yan-ling Liu; Xu Chen; Xi-ling Fan; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry Letters, 2023)

Marine osmium‑uranium‑sulfur isotope evidence for the interaction of volcanism and ocean anoxia during the Middle Pleistocene in the tropical Western Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Rui Zhang; Tiegang Li; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; Minglei Guan; Qi Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

A designed plasmid‐transition strategy enables rapid construction of robust and versatile synthetic exoelectrogens for environmental applications - Yang‐Yang Fan; Qiang Tang; Hong Sun; Han‐Qing Yu (Environmental Microbiology, 2022)
Genetic engineering is promising to expand the application scope of exoelectrogens in energy and environmental applications and plasmid vectors, as one type of fundamental tool, are intensively applied. Antibiotics are widely utilized for plasmid selection and maintenance; however, their utilization suffers from environmental concerns on the spread of resistance genes, elevated costs, inevitable genotypic instability and phenotypic heterogeneity. In this work, we establish an auxotrophic complementation system for stable plasmid maintenance without antibiotic association, in Shewanella oneidensis , an attractive model exoelectrogen. A plasmid‐transition strategy is designed to facilitate the rapid and efficient construction of the auxotrophic complementation system. Such a system not only enables the same intensive gene expression as the conventional antibiotic‐associated plasmid system but also exhibits remarkably superior robustness and stability. With this system, the menaquinone pool of the extracellular respiratory chain is enhanced first independently and further synergized by engineering the Mtr conduit, leading to significantly promoted extracellular electron transfer (EET) outputs (up to 10.33‐ and 2.97‐fold improvement in the maximum current density and the maximum output voltage) and heavy metal Cr(VI) reduction ability (5.15‐fold improvement). This work provides a robust and stable platform to engineer exoelectrogens for environmental applications.

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Bacteria-based nanosystems for enhanced antitumor therapy - Yu Han; Miao Fan; Dandan Han; Kun Ge; Jin Chang; Jinchao Zhang (Science China Life Sciences, 2022)

Lipin1 Alleviates Autophagy Disorder in Sciatic Nerve and Improves Diabetic Peripheral Neuropathy - Meijian Wang; Min Xie; Shuyan Yu; Pan Shang; Cong Zhang; Xiaolin Han; Cuiqin Fan; Li Chen; Xianghua Zhuang; Shihong Chen (Molecular Neurobiology, 2021)

Size Effect and Anisotropy in a Transversely Isotropic Rock Under Compressive Conditions - Kaihui Li; Zhen-Yu Yin; Dongya Han; Xiang Fan; Rihong Cao; Hang Lin (Rock Mechanics and Rock Engineering, 2021)

Evaluation of freeze–thaw erosion in Tibet based on the cloud model - Junfu Fan; Taoying Hu; Xiao Yu; Jiahao Chen; Liusheng Han; Yuke Zhou (Frontiers of Earth Science, 2021)

Fine mapping and candidate gene analysis of a major locus controlling ovule abortion and seed number per silique in Brassica napus L. - Yangmiao Jiao; Kunpeng Zhang; Guangqin Cai; Kaidi Yu; Olalekan Amoo; Shaoqing Han; Xiang Zhao; Hao Zhang; Limin Hu; Bingrui Wang; Chuchuan Fan; Yongming Zhou (Theoretical and Applied Genetics, 2021)

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

NestNet: a multiscale convolutional neural network for remote sensing image change detection - Xiao Yu; Junfu Fan; Jiahao Chen; Peng Zhang; Yuke Zhou; Liusheng Han (International Journal of Remote Sensing, 2021)

A new method for wellbore stability evaluation based on fractured carbonate reservoir rock breaking degree - Houbin Liu; Shuai Cui; Yingfeng Meng; Xu Han; Teng Liu; Yu Fan; Ye Tao; Anran Yu (Arabian Journal of Geosciences, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Association between selected urinary heavy metals and asthma in adults: a retrospective cross-sectional study of the US National Health and Nutrition Examination Survey - Xiuzhu Li; Yun Fan; Yan Zhang; Xiaomin Huang; Zhenyao Huang; Mingming Yu; Qiaoqiao Xu; Xiumei Han; Chuncheng Lu; Xinru Wang (Environmental Science and Pollution Research, 2021)

Rapid and highly efficient genomic engineering with a novel iEditing device for programming versatile extracellular electron transfer of electroactive bacteria - Yang‐Yang Fan; Qiang Tang; Yang Li; Feng‐He Li; Jing‐Hang Wu; Wen‐Wei Li; Han‐Qing Yu (Environmental Microbiology, 2021)
Summary The advances in synthetic biology bring exciting new opportunities to reprogram microorganisms with novel functionalities for environmental applications. For real‐world applications, a genetic tool that enables genetic engineering in a stably genomic inherited manner is greatly desired. In this work, we design a novel genetic device for rapid and efficient genome engineering based on the i ntron‐encoded homing‐endonuclease empowered genome editing (iEditing). The iEditing device enables rapid and efficient genome engineering in Shewanella oneidensis MR‐1, the representative strain of the electroactive bacteria group. Moreover, combining with the Red or RecET recombination system, the genome‐editing efficiency was greatly improved, up to approximately 100%. Significantly, the iEditing device itself is eliminated simultaneously when genome editing occurs, thereby requiring no follow‐up to remove the encoding system. Then, we develop a new extracellular electron transfer (EET) engineering strategy by programming the parallel EET systems to enhance versatile EET. The engineered strains exhibit sufficiently enhanced electron output and pollutant reduction ability. Furthermore, this device has demonstrated its great potential to be extended for genome editing in other important microbes. This work provides a useful and efficient tool for the rapid generation of synthetic microorganisms for various environmental applications.

PSO-SVM-based deep displacement prediction of Majiagou landslide considering the deformation hysteresis effect - Lei Zhang; Bin Shi; Honghu Zhu; Xiong Bill Yu; Heming Han; Xudong Fan (Landslides, 2021)

Critical roles of macrophages in pressure overload-induced cardiac remodeling - Dan Yang; Han-Qing Liu; Fang-Yuan Liu; Nan Tang; Zhen Guo; Shu-Qing Ma; Peng An; Ming-Yu Wang; Hai-Ming Wu; Zheng Yang; Di Fan; Qi-Zhu Tang (Journal of Molecular Medicine, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

Hydrogeochemical and statistical analysis of high fluoride groundwater in northern China - Fan Feng; Yongfeng Jia; Yu Yang; Huan Huan; Xinying Lian; Xiangjian Xu; Fu Xia; Xu Han; Yonghai Jiang (Environmental Science and Pollution Research, 2020)

Extracellular ATP affects cell viability, respiratory O2 uptake, and intracellular ATP production of tobacco cell suspension culture in response to hydrogen peroxide-induced oxidative stress - Qin-zheng Hou; Yu-pei Wang; Bao-qiang Fan; Kun Sun; Jun-yu Liang; Han-qing Feng; Ling-yun Jia (Biologia, 2020)

Occurrence of leaf spot caused by Nigrospora oryzae on red elephant grass in Chongqing, China - Yu-Zhu Han; Zi-wei Fan; Wei He; Jian Zhang (Journal of Plant Pathology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Ketamine Alleviates Fear Generalization Through GluN2B-BDNF Signaling in Mice - Muhammad Asim; Bo Hao; Yu-Han Yang; Bu-Fang Fan; Li Xue; Yan-Wei Shi; Xiao-Guang Wang; Hu Zhao (Neuroscience Bulletin, 2020)

RBM4 modulates the proliferation and expression of inflammatory factors via the alternative splicing of regulatory factors in HeLa cells - Wei-Yang Wang; Weili Quan; Fan Yang; Ya-Xun Wei; Jia-Jun Chen; Han Yu; Jie Xie; Yi Zhang; Zhan-Fei Li (Molecular Genetics and Genomics, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Investigations on the phytotoxicity of perfluorooctanoic acid in Arabidopsis thaliana - Lingling Fan; Jie Tang; Danfeng Zhang; Mingyue Ma; Yu Wang; Yi Han (Environmental Science and Pollution Research, 2020)

New anthraquinone and eurotinone analogue from the seeds of Senna obtusifolia and their inhibitory effects on human organic anion transporters 1 and 3 - Xu Pang; Li-Ming Wang; You-Cai Zhang; Li-Ping Kang; He-Shui Yu; Guan-Wei Fan; Li-Feng Han (Natural Product Research, 2019)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Toll-Like Receptor 4 Promotes Th17 Lymphocyte Infiltration Via CCL25/CCR9 in Pathogenesis of Experimental Autoimmune Encephalomyelitis - Ying Zhang; Jingjing Han; Meili Wu; Lu Xu; Yu Wang; Wen Yuan; Fang Hua; Hongbin Fan; Fuxing Dong; Xuebin Qu; Ruiqin Yao (Journal of Neuroimmune Pharmacology, 2019)

Behavioural, physiological and molecular changes in alloparental caregivers may be responsible for selection response for female reproductive investment in honey bees - Fan Wu; Chuan Ma; Bin Han; Lifeng Meng; Han Hu; Yu Fang; Mao Feng; Xufeng Zhang; Olav Rueppell; Jianke Li (Molecular Ecology, 2019)
Reproductive investment is a central life history variable that influences all aspects of life. Hormones coordinate reproduction in multicellular organisms, but the mechanisms controlling the collective reproductive investment of social insects are largely unexplored. One important aspect of honey bee ( Apis mellifera ) reproductive investment consists of raising female‐destined larvae into new queens by alloparental care of nurse bees in form of royal jelly provisioning. Artificial selection for commercial royal jelly production over 40 years has increased this reproductive investment by an order of magnitude. In a cross‐fostering experiment, we establish that this shift in social phenotype is caused by nurse bees. We find no evidence for changes in larval signalling. Instead, the antennae of the nurse bees of the selected stock are more responsive to brood pheromones than control bees. Correspondingly, the selected royal jelly bee nurses are more attracted to brood pheromones than unselected control nurses. Comparative proteomics of the antennae from the selected and unselected stocks indicate putative molecular mechanisms, primarily changes in chemosensation and energy metabolism. We report expression differences of several candidate genes that correlate with the differences in reproductive investment. The functional relevance of these genes is supported by demonstrating that the corresponding proteins can competitively bind one previously described and one newly discovered brood pheromone. Thus, we suggest several chemosensory genes, most prominently OBP16 and CSP4, as candidate mechanisms controlling queen rearing, a key reproductive investment, in honey bees. These findings reveal novel aspects of pheromonal communication in honey bees and explain how sensory changes affect communication and lead to a drastic shift in colony‐level resource allocation to sexual reproduction. Thus, pheromonal and hormonal communication may play similar roles for reproductive investment in superorganisms and multicellular organisms, respectively.

The polymorphism of SMAD3 rs1065080 is associated with increased risk for knee osteoarthritis - Chao Lu; Jin Shu; Yan Han; Xiao Yu Ren; Ke Xu; Hua Fan; Ying Pu Chen; Kan Peng (Molecular Biology Reports, 2019)

Identification of a lytic Pseudomonas aeruginosa phage depolymerase and its anti-biofilm effect and bactericidal contribution to serum - Liyuan Mi; Yannan Liu; Can Wang; Tongtong He; Shan Gao; Shaozhen Xing; Yong Huang; Hang Fan; Xianglilan Zhang; Wengong Yu; Zhiqiang Mi; Yigang Tong; et al. (Virus Genes, 2019)

The evolution of tea spatial agglomeration in China: An analysis based on different geographical scales - Han-chu Liu; Jie Fan; Yu-xi Zeng; Wen-zhao Wang (Journal of Mountain Science, 2018)

Exploring inhibition mechanism and nature of lipase by Ligupurpuroside A extracted from Ku-Ding tea - Yu Fan; Yang Xu; Qing-Guo Han; Liang-Liang Shen; Hong Xu; Zhi-Bing Wu; Xu Xu; Ming Ying; Zhen-Dan He; Zhang-Li Hu (Medicinal Chemistry Research, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Synthesis and anticonvulsant activity of some novel 7-(benzylamino) -1H-benzo[b][1,4]diazepine-2,4(3H, 5H)-dione derivatives - Yun-Peng Shao; Rong-Bi Han; Hui-Fan Wu; Feng-Yu Piao (Medicinal Chemistry Research, 2018)

Decreased Methylation Level of H3K27me3 Increases Seizure Susceptibility - Zhongcheng Wang; Yusong Zhang; Jian Fang; Fang Yu; Duanhe Heng; Yuanteng Fan; Jian Xu; Biwen Peng; Wanhong Liu; Song Han; Xiaohua He (Molecular Neurobiology, 2017)

Interacting effects of multiple factors on the morphological evolution of the meandering reaches downstream the Three Gorges Dam - Jianqiao Han; Wei Zhang; Yongyang Fan; Mengqing Yu (Journal of Geographical Sciences, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

High-resolution mapping of QTL for fatty acid composition in soybean using specific-locus amplified fragment sequencing - Bin Li; Shengxü Fan; Fukuan Yu; Ying Chen; Shengrui Zhang; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Theoretical and Applied Genetics, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Effects of aluminum trichloride on the cartilage stimulatory growth factors in rats - Fan Zhang; Xudong Sun; Hongyan Yu; Xu Yang; Miao Song; Yanfei Han; Yanfei Li; Yanzhu Zhu (BioMetals, 2017)

Molecular signal networks and regulating mechanisms of the unfolded protein response - Jing Gong; Xing-zhi Wang; Tao Wang; Jiao-jiao Chen; Xiao-yuan Xie; Hui Hu; Fang Yu; Hui-lin Liu; Xing-yan Jiang; Han-dong Fan (Journal of Zhejiang University-SCIENCE B, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Passive sampling of polybrominated diphenyl ethers in indoor and outdoor air in Shanghai, China: seasonal variations, sources, and inhalation exposure - Wenliang Han; Tao Fan; Binhua Xu; Jialiang Feng; Gan Zhang; Minghong Wu; Yingxin Yu; Jiamo Fu (Environmental Science and Pollution Research, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Analysis of additive and epistatic quantitative trait loci underlying fatty acid concentrations in soybean seeds across multiple environments - Shengxu Fan; Bin Li; Fukuan Yu; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Euphytica, 2015)
Soybean is one of the most important oilseed crops in the world. The soybean oil contains various fatty acids. Their concentrations determine the quality and nutritional value of soybean oil. On the other hand, quantitative trait loci (QTL) mapping for the concentrations of soybean predominant fatty acids could provide the genetic basis for soybean fatty acid composition. In this study, a soybean genetic linkage map was constructed based on 161 polymorphic SSR markers in recombinant inbred lines (RILs) derived from a cross of cv. Luheidou2 × Nanhuizao. By using this map, 35 additive QTLs underlying individual fatty acid concentrations were identified in single environment, while 17 additive QTLs were identified underlying specific fatty acids across multiple environments or underlying multiple fatty acids. Fifteen of the 52 loci were found to be novel loci, explaining 5–24 % of phenotypic variation. Moreover, 25 epistatic QTLs were identified and explained a high phenotypic variation for the fatty acid concentrations, suggesting an essential role of epistatic effect for fatty acid concentrations. The identification of additive and epistatic QTLs suggested a complex network for soybean fatty acid concentrations, and will facilitate the understanding for fatty acid accumulation.

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

DLEC1, a 3p tumor suppressor, represses NF-κB signaling and is methylated in prostate cancer - Lian Zhang; Qian Zhang; LiLi Li; Zhaohui Wang; Jianming Ying; Yu Fan; Qun He; Tianjing LV; Wenke Han; Jun Li; Yang Yang; Ben Xu; et al. (Journal of Molecular Medicine, 2015)

The effects of complete submergence on the morphological and biomass allocation response of the invasive plant Alternanthera philoxeroides - Shufeng Fan; Haihao Yu; Chunhua Liu; Dan Yu; Yuqin Han; Ligong Wang (Hydrobiologia, 2015)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

Synthesis and anticonvulsant evaluation of some new 1,3,4,5-tetrahydro-6-alkoxy-2H-1-benzazepin-2-one derivatives - Rong-Bi Han; Yun-Peng Shao; Hui-Fan Wu; Duo Zhang; Feng-Yu Piao (Medicinal Chemistry Research, 2014)

Nontoxic piperamides and their synthetic analogues as novel antifouling reagents - Xiang-Zhong Huang; Ying Xu; Yi-Fan Zhang; Yu Zhang; Yue Him Wong; Zhuang Han; Yan Yin; Pei-Yuan Qian (Biofouling, 2014)

Assimilating ASAR data for estimating soil moisture profile using an ensemble Kalman filter - Fan Yu; Haitao Li; Haiyan Gu; Yanshun Han (Chinese Geographical Science, 2013)

Two endosymbiotic bacteria, Wolbachia and Arsenophonus, in the brown planthopper Nilaparvata lugens - Lv-Yu Qu; Yi-Han Lou; Hai-Wei Fan; Yu-Xuan Ye; Hai-Jian Huang; Meng-Qi Hu; Ya-Ni Zhu; Chuan-Xi Zhang (Symbiosis, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Characteristics and genesis of microbial lumps in the Maozhuang Stage (Cambrian Series 2), Shandong Province, China - RenChao Yang; AiPing Fan; ZuoZhen Han; NaiJie Chi; Yu Han (Science China Earth Sciences, 2013)

Down-regulation of platelet-derived growth factor-D expression blockades NF-κB pathway to inhibit cell proliferation and invasion as well as induce apoptosis in esophageal squamous cell carcinoma - Yu Han; Xiao-He Guo; Qing-Fen Zheng; Yan-Li Zhu; Ying-Ying Fan; Xiu-Ying Zhang (Molecular Biology Reports, 2013)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)

Retrieval of aerosol optical depth over bright targets in the urban areas of North China during winter - ShenShen Li; LiangFu Chen; JinHua Tao; Dong Han; ZhongTing Wang; Lin Su; Meng Fan; Chao Yu (Science China Earth Sciences, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Molecular characterization of the porcine MTPAP gene associated with meat quality traits: chromosome localization, expression distribution, and transcriptional regulation - Xuelei Han; Tengfei Jiang; Lei Yu; Cuiping Zeng; Bin Fan; Bang Liu (Molecular and Cellular Biochemistry, 2012)

Synthesis, Photo- and Electro-Luminescence of 3-Benzoxazol-2-yl-Coumarin Derivatives - Yuling Zhao; Tianzhi Yu; Youzhi Wu; Hui Zhang; Duowang Fan; Zunwei Gan; Liangliang Yang; Xiaoqian Han; Yumei Zhang (Journal of Fluorescence, 2012)

BcMF20, a putative pollen-specific transcription factor from Brassica campestris ssp. chinensis - Yingyan Han; Aihong Zhang; Li Huang; Xiaolin Yu; Kai Yang; Shuangxi Fan; Jiashu Cao (Molecular Biology Reports, 2011)

Effects of SLCO1B1 polymorphisms on the pharmacokinetics and pharmacodynamics of repaglinide in healthy Chinese volunteers - Jiake He; Zhixia Qiu; Ning Li; Yang Yu; Yang Lu; Deen Han; Tingting Li; Di Zhao; Wei Sun; Fang Fang; Jianheng Zheng; Hongwei Fan; et al. (European Journal of Clinical Pharmacology, 2011)

Effective kinetics of schisandrin B on serum/hepatic triglyceride and total cholesterol levels in mice with and without the influence of fenofibrate - Si-Yuan Pan; Hang Dong; Bao-feng Guo; Yi Zhang; Zhi-Ling Yu; Wang-Fun Fong; Yi-Fan Han; Kam-Ming Ko (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Species-specific and needle age-related responses of photosynthesis in two Pinus species to long-term exposure to elevated CO2 concentration - Yu-Mei Zhou; Cun-Guo Wang; Shi-Jie Han; Xu-Bing Cheng; Mai-He Li; A-Nan Fan; Xiu-Xiu Wang (Trees, 2011)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

Engineering geology and stability of the Jishixia landslide, Yellow River, China - Fan-yu Zhang; Gao Liu; Wen-wu Chen; Wen-feng Han; Shi-biao Bai (Bulletin of Engineering Geology and the Environment, 2010)

Function of Drosophila mob2 in photoreceptor morphogenesis - Ling-Yu Liu; Cheng-Han Lin; Seng-Sheen Fan (Cell and Tissue Research, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Involvement of MGr1-Ag/37LRP in the vincristine-induced HIF-1 expression in gastric cancer cells - Lili Liu; Xiaoxuan Ning; Li Sun; Yongquan Shi; Shuang Han; Changcun Guo; Yu Chen; Shiren Sun; Fang Yin; Kaichun Wu; Daiming Fan (Molecular and Cellular Biochemistry, 2007)

Inhibitory effects of a specific phage-displayed peptide on high peritoneal metastasis of gastric cancer - Feihu Bai; Jie Liang; Jun Wang; Yongquan Shi; Kedong Zhang; Shuhui Liang; Liu Hong; Huihong Zhai; Yuanyuan Lu; Yu Han; Fang Yin; Kaichun Wu; et al. (Journal of Molecular Medicine, 2007)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

Note: Identification of Three Novel Insertion/Deletion Mutations in Wilson Disease's Gene - Yuxin Fan; Long Yu; Yongzhu Han; Mingshan Ren; Renmin Yang; Shouyuan Zhao (Biochemical Genetics, 2004)